A Multiresolution PDE-Based Deformable Surface for Medical Imaging Applications (International Journal of Biomedical Imaging)
We recently developed a multiresolution PDE-based deformable surface whose deformation behavior is governed by partial differential equations (PDEs) such as the weighted minimal surface flow. Comparing with the level-set approach, our new model has better control of the mesh quality and model resolution, and is much simpler to implement since all the computations are local. The new deformable model is very useful for a variety of medical imaging applications including boundary reconstruction, surface visualization, data segmentation, and topology discovery. In this paper, we demonstrate both the accuracy and robustness of our model on areas such as medical image segmentation through a number of experiments on both real (MRI/CT) and synthetic volumetric datasets.